ACCOUNTING, BOOK KEEPING, ACCOUNTING, ACCURACY, ACCOUNTABILITY, VERANTWORTUNG - Bobbio Rosas, Emilio Gustavo (2016)
Accounting is often viewed as a technical activity of consistent numerical data registrations, as an accounts book keeping. Sometimes a little more content is given and including analysis of information with the subsequent issuance of findings and recommendations, which, together with investigations, would raise the activity at a scientific level. However, the ethical and social responsibility aspects associated with the accounting profession are often forgotten. This becomes more noticeable when making a multilingual analysis of the terms involved. This paper clarifies words like accuracy and accountability and links them to the German word Verantwortung, allowing a better understanding of everything that involves the accounting profession to society